Research progress on preparation methods of water-soluble polyaniline. (April 2023) - Xiao, Yuansong; Wang, Yanmin; Wu, Xueliang; Ma, Yong
The application of polyaniline (PANI) in various fields is greatly limited by its poor solubility in water.Many methods which could elevate PANI water-soluble ability were used by researchers to expand its application range. In this paper, the research progress of the commonly used preparation methods of water-soluble PANI in recent years is reviewed. The main preparation methods of water-soluble PANI are categorized into four types including monomer modification, controlling the polymerization process, introducing water-soluble groups or substances, macromolecular reaction. They are composed of aniline derivative method, copolymerization, emulsion polymerization method, dispersion polymerization method, acid doping method, compound method, ATRP method. The principles of various methods to achieve water-solubility of PANI are introduced, the research on each preparation method reported before are introduced and their advantages and disadvantages are summarized.